Inside the Fed : monetary policy and its management, Martin through Greenspan to Bernanke - Axilrod, S. H. (Cambridge, Mass. : MIT Press, 2009)
This new, post-financial meltdown edition offers his assessment of the Fed action (and inaction) during the crisis and expanded coverage of the Fed in the Bernanke era. In this revised edition, Axilrod gives an account of the Fed dramatic, even mind-bending, experiences in the great credit crisis of 2007-2009. He assesses the full range of the Fed unusual and innovative actions during the crisis and the beginnings of its aftermath. He questions whether the Fed used its monetary and regulatory powers to full effect to minimize and contain the disruption of the nation and the world financial stability. In later chapters he also reevaluates the image, stature, and structure of the Fed in the aftermath of the crisis and the new comprehensive financial legislation subsequently enacted. Great leadership in monetary policy, Axilrod says, is determined not by pure economic sophistication but by the ability to push through political and social barriers to achieve a paradigm shift in policy and by the courage and bureaucratic moxie to pull it off.
Overview of policy management and managers -- In Bill Martin's time -- Arthur Burns and the struggle against inflation -- The Miller interlude -- Paul Volcker and the victory over inflation -- The Greenspan years and after -- The Fed and its image -- Summing up and looking ahead.
Includes bibliographical references (p. [191]-198) and index.
rpm 17/05/13
Loans
Keywords: Monetary policy -- United States; Board of Governors of the Federal Reserve System (U.S.); Banks and banking, Central -- United States; Federal Reserve banks